Parental control application that can remotely access using Short Messaging Service (SMS) / Muhammad Syafiq Shaharudin - Shaharudin, Muhammad Syafiq (Faculty of Computer and Mathematical Sciences, 2018)
There are a lot of existing parental control applications that are available in applications stores for mobile operating system. In every parental control has different features and it specifications. Every parental control applications have its own pros and cons. For this project which is differ than other existing parental control applications which it is aimed to create an application for android operating system. Although the existing parental control applications provide many restrictions but they do not offer a complete protection and security. As kids nowadays are clever and know how to make use of a smartphone. The Short Messaging Service (SMS) can entered command to control other phones. This project is using software development life cycle (SDLC) waterfall model. It involves five important phases. The results of this project will be done in functionality testing to make sure this project well developed. Therefore, this project has developed a parental control mobile device application on android operating system for children that using SMS command for the purpose of monitoring and controlling the children’s activities. This project can be extended by develop application for parent’s side that can send SMS by just touch a button and send message automatically.